An Investigation of Memory for Daily Computing Events - Czerwinski, Mary; Horvitz, Eric (People and Computers XVI, Proceedings of HCI 2002, 2002)
In pursuit of computational tools for augmenting computer users’ abilities to interleave multiple tasks, we examined computer users’ ability to identify and recall computing events deemed to be important, both with and without supportive reminder tools. Memory for events occurring during computer sessions was studied both 24 hours after an initial taped session and again after a one-month period of time. Results show that memory for important computing events is fragile and that software tools could be used to augment users’ memories of how they have spent their time while computing. In addition, we observed that approximately half of the events that users identified as important could be identified automatically with available computational methods, and an attempt was made to characterize the nature of the remaining events. Finally, in a probe of alternate designs for reminding systems, we found that users typically preferred to see snapshots of their computing events in a prototype reminder system, without audio, as opposed to a full video version of an event reminder system.